The legal field of ethnic policy in the Republic of Tyva since 1991 - Tarbastaeva, Inna S. (The New Research of Tuva, 2016)
The article examines the legal regulation of regional ethnonational policy in the Republic of Tuva in 1991-2016. We mark out three periods which correspond to the priorities federal and regional powers chose to determine their ethnic policies.During the first of the three periods (1991-1996) legislators followed the logic of endowing the region’s titular ethnicity with a status of a core community, with other ethnic groups to develop by clustering around it. This was probably the most fruitful period for passing regional legislation which dealt with the issues of ethnic policy.The second of the three periods (1996-2013) followed the practice of aligning regional ethnic policy with the general developments in the federal legal space. At the same time, specific ethnosocial situation in Tuva was taken into account. The local authorities focused on developing the region’s titular ethnicity – Tuvans, while guaranteeing full equality of all ethnocultural communities. Legislation largely follows regional priorities that might have deviated from the federal course. This allowed Tuva’s authorities to pursue a flexible policy, matching the specific needs of a particular interethnic community.In the third period (since 2013), ethnic policy is focused on preserving and developing Tuva’s ethnocultural diversity, including the support of Russian language and ethnic Russians. At the moment, more than 10 laws dealing with these issues are in effect in the region, as well as a number of decrees of the Head of the republic, executive orders of its Cabinet of Ministers and special-purpose programs. In this article, we closely examine the regional program on “Strengthening the civic unity and ethnocultural development of ethnicities in the Republic of Tuva” (2013), as well as events organized under the aegis of this program. This proves the commitment of regional authorities to prioritizing ethnic culture and interethnic relations in the Republic of Tuva.Overall, regional legislation has reflected the change in key priorities of regional policy in Tuva – from focusing on the rights of titular ethnicity in the 1990s to supporting ethnocultural variety on all levels, including the rights of ethnic Russians.
Keywords: Tuva; Tuvans; ethnic policy; ethnonational policy; ethnic community; legal status of ethnicities; regional policy; post-Soviet period; Russians in Tuva